The Genomics of Neonatal Abstinence Syndrome - Cole, F. Sessions; Wegner, Daniel J.; Davis, Jonathan M. (Frontiers in Pediatrics, 2017)
Significant variability has been observed in the development and severity of Neonatal Abstinence Syndrome (NAS) among neonates exposed to prenatal opioids. Since maternal opioid dose does not appear to correlate directly with neonatal outcome, maternal, placental, and fetal genomic variants may play important roles in NAS. Previous studies in small cohorts have demonstrated associations of variants in maternal and infant genes that encode the µ-opioid receptor (OPRM1), catechol-o-methyl transferase (COMT), and prepronociceptin (PNOC) with a shorter length of hospital stay and less need for treatment in neonates exposed to opioids in utero. Consistently falling genomic sequencing costs and computational approaches to predict variant function will permit unbiased discovery of genomic variants and gene pathways associated with differences in maternal and fetal opioid pharmacokinetics and pharmacodynamics and with placental opioid transport and metabolism. Discovery of pathogenic variants should permit better delineation of the risk of developing more severe forms of NAS. This review provides a summary of the current role of genomic factors in the development of NAS and suggests strategies for further genomic discovery.